Issues Causing the Solidarity and Unity of Indonesia Perspective of Islamic Religious Education - Asmiatin, Asmiatin; St Wardah Hanafie Das (Nusantara Education, 2024)
Abstract: This study examines the role of Islamic Religious Education (PAI) in strengthening Indonesia's unity and unity, which is often threatened by problems such as radicalization, social polarization, and intolerance. Given the diversity of religions, ethnicities, and cultures in Indonesia, PAI has a responsibility to instill Islamic values that emphasize peace, tolerance, and unity. This study uses a literature review approach to identify various strategies that can be applied in PAI to reduce social tension and strengthen interfaith relationships. The strategies discussed include strengthening Islamic ukhuwah, the implementation of religious moderation, Islamic character education, digital literacy, and the integration of local values in PAI learning. The findings of the study show that PAI, through its approach to religious moderation and character education, can play an important role in shaping a more inclusive and respectful society, while strengthening national unity. In addition, digital literacy applied wisely can help address the dissemination of information that undermines unity, while the integration of local values in PAI offers an approach that is relevant to Indonesian culture. This article emphasizes that PAI has great potential as an agent of change in easing polarization and creating a harmonious society in the midst of diversity